2018
DOI: 10.1007/s00394-018-1670-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bovine colostrum supplementation on intestinal injury and circulating intestinal bacterial DNA following exercise in the heat

Abstract: Purpose Exercise-induced changes in intestinal permeability are exacerbated in the heat. The aim of this study was to determine the effect of 14 days of bovine colostrum (Col) supplementation on intestinal cell damage (plasma intestinal fatty acid-binding protein, I-FABP) and bacterial translocation (plasma bacterial DNA) following exercise in the heat. Methods In a double-blind, placebo-controlled, crossover design, 12 males completed two experimental arms (14 days of 20 g/day supplementation with Col or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 47 publications
6
67
0
Order By: Relevance
“…A previous systematic review has suggested an exercise-induced hyperthermia threshold of 38.6°C T core for GI barrier integrity loss (DSAT, I-FABP and endotoxin) to be commonplace (>50% incidence) and of 39.0°C for GI barrier integrity loss to be universal (100% incidence; Pires et al, 2017). Consistently, previous research supports the notion that MT biomarkers (endotoxin) are less responsive to subtle alterations in GI barrier integrity that were otherwise detected by the DSAT or I-FABP following exercise (March et al, 2019;Snipe et al, 2017Snipe et al, , 2018. Positively, no GI barrier integrity or MT biomarker displayed statistical heteroskedasticity in this EHST model, suggestive that absolute reliability was not dependent upon the magnitude of biomarker response.…”
Section: Limitationssupporting
confidence: 80%
See 4 more Smart Citations
“…A previous systematic review has suggested an exercise-induced hyperthermia threshold of 38.6°C T core for GI barrier integrity loss (DSAT, I-FABP and endotoxin) to be commonplace (>50% incidence) and of 39.0°C for GI barrier integrity loss to be universal (100% incidence; Pires et al, 2017). Consistently, previous research supports the notion that MT biomarkers (endotoxin) are less responsive to subtle alterations in GI barrier integrity that were otherwise detected by the DSAT or I-FABP following exercise (March et al, 2019;Snipe et al, 2017Snipe et al, , 2018. Positively, no GI barrier integrity or MT biomarker displayed statistical heteroskedasticity in this EHST model, suggestive that absolute reliability was not dependent upon the magnitude of biomarker response.…”
Section: Limitationssupporting
confidence: 80%
“…This method is particularly favorable given that the phyla Firmicutes and Bacteroidetes comprise >90% of the GI microbiome ( Bacteroides ; Huttenhower et al, ) and <5% of the plasma microbiome (Paisse et al, 2016). Utilizing this hypothesis, March et al () reported that the plasma Bacteroides /16S DNA ratio tended to increase (~25%; p = .07) following a 1‐hr moderate intensity (70% VO 2max ) run in the heat (30°C), though large interindividual variability in responses were evident. In this study, the Bacteroides /16S DNA ratio was unchanged following the EHST and appeared to be systematically lower following exercise in trial two (but not the Δ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations